This repository has been archived on 2024-10-22. You can view files and clone it, but cannot push or open issues or pull requests.
OM/Claudio_Maggioni_4/Claudio_Maggioni_4.md

151 lines
5.3 KiB
Markdown
Raw Normal View History

2021-05-25 08:41:07 +00:00
<!-- vim: set ts=2 sw=2 et tw=80: -->
---
2021-05-25 08:43:02 +00:00
title: Homework 4 -- Optimization Methods
2021-05-25 08:41:07 +00:00
author: Claudio Maggioni
header-includes:
- \usepackage{amsmath}
- \usepackage{hyperref}
- \usepackage[utf8]{inputenc}
- \usepackage[margin=2.5cm]{geometry}
- \usepackage[ruled,vlined]{algorithm2e}
- \usepackage{float}
- \floatplacement{figure}{H}
- \hypersetup{colorlinks=true,linkcolor=blue}
---
\maketitle
# Exercise 1
## Exercise 1.1
The lagrangian is the following:
$$L(X,\lambda) = f(X) - \lambda \left(c(x) - 0\right) = -3x^2 + y^2 + 2x^2 +
2(x+y+z) - \lambda x^2 - \lambda y^2 -\lambda z^2 + \lambda =$$$$= (-3 -\lambda)x^2 + (1-
\lambda)y^2 + (2-\lambda)z^2 + 2 (x+y+z) + \lambda$$
The KKT conditions are the following:
First we have the condition on the partial derivatives of the Lagrangian w.r.t.
$X$:
$$\nabla_X L(X,\lambda) = \begin{bmatrix}(-3-\lambda)x^* + 1\\(1-\lambda)y^* +
1\\(2-\lambda)z^* + 1\end{bmatrix} = 0 \Leftrightarrow
\begin{bmatrix}x^*\\y^*\\z^*\end{bmatrix} =
\begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\-\frac{1}{2-\lambda}\end{bmatrix}$$
Then we have the conditions on the equality constraint:
$$c(X) = {x^*}^2 + {y^*}^2 + {z^*}^2 - 1 = 0 \Leftrightarrow \|X^*\| = 1$$
$$\lambda^* c(X^*) = 0 \Leftarrow c(X^*) = 0 \text{ which is true if the above
condition is true.}$$
Since we have no inequality constraints, we don't need to apply the KKT
conditions realated to inequality constraints.
## Exercise 1.2
To find feasible solutions to the problem, we apply the KKT conditions. Since we
have a way to derive $X^*$ from $\lambda^*$ thanks to the first KKT condition,
we try to find the values of $\lambda$ that satisfies the second KKT condition:
$$c(x) = \left( \frac{1}{3+\lambda} \right)^2 + \left( -\frac{1}{1-\lambda} \right)^2 +
\left(-\frac{1}{2-\lambda}\right)^2 - 1 =
\frac{1}{(3+\lambda)^2} + \frac{1}{(1-\lambda)^2} + \frac{1}{(2-\lambda)^2} - 1 =$$$$=
\frac{(1-\lambda)^2(2-\lambda)^2 + (3+\lambda)^2(2-\lambda)^2 +
(3+\lambda)^2
(1-\lambda)^2 - (3+\lambda)^2 (1-\lambda)^2 (2-\lambda)^2}{(3+\lambda)^2
(1-\lambda)^2 (2-\lambda)^2} = 0
\Leftrightarrow$$$$\Leftrightarrow
(1-\lambda)^2(2-\lambda)^2 + (3+\lambda)^2(2-\lambda)^2 +
(3+\lambda)^2
(1-\lambda)^2 - (3+\lambda)^2 (1-\lambda)^2 (2-\lambda)^2 = 0
\Leftrightarrow$$$$\Leftrightarrow
(\lambda^4 - 6\lambda^3 + 13\lambda^2 - 12\lambda + 16) +
(\lambda^4 + 2\lambda^3 - 11\lambda^2 - 12\lambda + 36) +
(\lambda^4 + 4\lambda^3 - 2\lambda^2 - 12\lambda + 9)$$$$
2021-05-26 10:00:01 +00:00
+ (\lambda^6 -14\lambda^4 +12\lambda^3 +49\lambda^2 -84\lambda + 36) = $$$$
=-\lambda^6 +17\lambda^4 -12\lambda^3 -49\lambda^2 +48\lambda +13 = 0
2021-05-25 08:41:07 +00:00
\Leftrightarrow $$$$ \Leftrightarrow
\lambda = \lambda_1 \approx -0.224 \lor
\lambda = \lambda_2 \approx -1.892 \lor
\lambda = \lambda_3 \approx 3.149 \lor
\lambda = \lambda_4 \approx -4.035$$
We then compute $X$ from each solution and evaluate the objective each time:
$$X = \begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\
-\frac{1}{2-\lambda}\end{bmatrix}
\Leftrightarrow$$$$\Leftrightarrow
X = X_1 \approx \begin{bmatrix}0.360\\-0.817\\-0.450\end{bmatrix} \lor
X = X_2 \approx \begin{bmatrix}0.902\\-0.346\\-0.257\end{bmatrix} \lor
X = X_3 \approx \begin{bmatrix}0.163\\0.465\\0.870\end{bmatrix} \lor
X = X_4 \approx \begin{bmatrix}-0.966\\-0.199\\-0.166\end{bmatrix}$$
$$f(X_1) = -1.1304 \;\; f(X_2) = -1.59219 \;\; f(X_3) = 4.64728 \;\; f(X_4) =
-5.36549$$
2021-05-25 12:55:19 +00:00
## Exercise 1.3
To find the optimal solution, we choose $(\lambda_4, X_4)$ since $f(X_4)$ is the
smallest objective
2021-05-25 08:41:07 +00:00
value out of all the feasible points. Therefore, the solution to the
minimization problem is:
$$X \approx \begin{bmatrix}-0.966\\-0.199\\-0.166\end{bmatrix}$$
2021-05-25 12:55:19 +00:00
# Exercise 2
## Exercise 2.1
To reformulate the problem, we first rewrite the explicit values of $G$, $c$,
$A$ and $b$:
2021-05-25 19:09:29 +00:00
$$G = 2 \cdot \begin{bmatrix}3&0&0\\2&2.5&0\\1&2&2\end{bmatrix}$$
$$c = \begin{bmatrix}-8\\-3\\-3\end{bmatrix}$$
2021-05-25 12:55:19 +00:00
$$A = \begin{bmatrix}1&0&1\\0&1&1\end{bmatrix}$$
$$b = \begin{bmatrix}3\\0\end{bmatrix}$$
2021-05-25 08:41:07 +00:00
2021-05-25 19:09:29 +00:00
Then, using these variable values and the formulation given on the assignment
sheet the problem is restated in this new form.
2021-05-25 08:41:07 +00:00
2021-05-25 19:09:29 +00:00
## Exercise 2.2
2021-05-25 08:41:07 +00:00
2021-05-25 19:09:29 +00:00
The lagrangian for this problem is the following:
2021-05-25 08:41:07 +00:00
2021-05-25 19:09:29 +00:00
$$L(x, \lambda) = \frac12\langle x, Gx\rangle + \langle x, c \rangle - \lambda
(Ax - b) =$$$$= \begin{bmatrix}x_1&x_2&x_3\end{bmatrix}
\begin{bmatrix}3&0&0\\2&2.5&0\\1&2&2\end{bmatrix}
\begin{bmatrix}x_1\\x_2\\x_3\end{bmatrix} +
\begin{bmatrix}x_1&x_2&x_3\end{bmatrix}
\begin{bmatrix}-8\\-3\\-3\end{bmatrix} - \lambda
\left(\begin{bmatrix}1&0&1\\0&1&1\end{bmatrix}
\begin{bmatrix}x_1\\x_2\\x_3\end{bmatrix} -
\begin{bmatrix}3\\0\end{bmatrix}\right)$$
The KKT conditions are the following:
First we have the condition on the partial derivatives of the Lagrangian w.r.t.
$X$:
$$\nabla_x L(x, \lambda) = Gx + c - A^T \lambda = \begin{bmatrix}3 x_1 - 8 +
\lambda_1\\ 2x_1 + 2.5 x_2 - 3 + \lambda_2\\x_1 + 2x_2 + 2x_3 - 3 + \lambda_1
+ \lambda_2\end{bmatrix} > 0$$
Then we have the conditions on the equality constraint:
$$Ax - b = 0 \Leftrightarrow \begin{bmatrix}x_1 + x_3\\x_2 + x_3\end{bmatrix} =
\begin{bmatrix}3\\0\end{bmatrix}$$
Then we have the conditions on the equality constraint:
$$\lambda^T (Ax - b) = 0 \Leftarrow Ax - b = 0 \text{ which is true if the above
condition is true.}$$
Since we have no inequality constraints, we don't need to apply the KKT
conditions realated to inequality constraints.